(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Every household’s need for clean water is important for daily activities. The increase in demand then increased during the pandemic and climate change which caused prolonged drought. This increase has a direct impact on economic, environmental and health problems. Therefore, it is necessary to pay attention to the efficiency of clean water use so that all demands for clean water are still met without incurring additional costs. The innovation offered is a prototype design for a water treatment installation that has been built so that it becomes a design guide and educational material for the local community. To make efficient use of clean water, water treatment is needed from handwashing or bathroom waste so that it can be reused for watering plants and cleaning cages. The aim of this activity is to provide education to the public about waste processing or water treatment in bathroom wastewater. The target of the activity is to provide an understanding of the importance of using clean water and the efficiency of waste processing which has a positive economic and environmental impact on society. The methods used in this activity include socializing the importance of using clean water and the efficiency of waste processing as well as direct work on water treatment installations. The result of this activity is that the people of RT 18/RW 007 can reuse waste water so that there is efficient use of clean water. — Kebutuhan air bersih tiap rumah tanggah penting untuk aktifitas sehari-hari. Peningkatan kebutuhan kemudian bertambah pada masa pandemi serta perubahan iklim yang menyebabkan kemarau yang berkepanjangan. Peningkatan ini berdampak langsung pada masalah ekonomi maupun lingkungan serta kesehatan. Oleh karena itu Efisiensi penggunaan air bersih perlu diperhatikan sehingga semua tuntutan kebutuhan air bersih tetap terpenuhi dengan tidak mengeluarkan biaya tambahan. Inovasi yang ditawarkan adalah sebuah desain prototype instalasi water treatmen yang terbangun sehingga menjadi panduan desain dan bahan edukasi bagi masyarakat sekitar. Untuk melakukan efisiensi penggunaan air bersih diperlukan water treatment dari buangan air cuci tangan atau kamar mandi sehingga bisa digunakan kembali untuk penyiraman tanaman dan pembersihan kandang. Tujuan dari kegiatan ini adalah untuk memberikan edukasi bagi masyarakat tentang pengolahan limbah atau water treatment pada air buangan kamar mandi. Sasaran kegiatan adalah pemberian pemahaman tentang pentingnya penggunaan air bersih serta efisiensi dari pengolahan limbah yang memberi dampak positif dari segi ekonomi maupun lingkungan bagi masyarakat. Metode yang digunakan dalam kegiatan ini meliputi sosialisasi pentingnya penggunaan air bersih serta efisiensi dari pengolahan limbah serta pengerjaan langsung instalasi water treatmen. Hasil dari kegiatan ini adalah masyarakat RT 18/RW 007 dapat memanfaatkan kembali air buangan sehingga terjadi efisiensi penggunaan air bersih.